2022
DOI: 10.1111/odi.14360
|View full text |Cite
|
Sign up to set email alerts
|

The homeostasis and therapeutic applications of innate and adaptive immune cells in periodontitis

Abstract: ObjectivesPeriodontitis (PD) is one of the most common dental disorders. This chronic oral inflammation is caused by complicated interrelations between bacterial infections, dysregulated immune reactions, and environmental risk factors. A dysregulated immune response can lead to inflammatory bone resorption by allowing the recruitment of pro‐inflammatory immune cells to the periodontal tissues.SubjectsThe recruitment of innate and adaptive immune cells in PD initiates the acute and following chronic inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 142 publications
0
0
0
Order By: Relevance
“…4,5 Studies have shown that both negative regulation of inflammatory cells and interventions aimed at increasing anti-inflammatory cells can assist in therapeutic applications for periodontitis. 6 Therefore, it is of interest to explore effective molecular targets for immune cell regulation.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Studies have shown that both negative regulation of inflammatory cells and interventions aimed at increasing anti-inflammatory cells can assist in therapeutic applications for periodontitis. 6 Therefore, it is of interest to explore effective molecular targets for immune cell regulation.…”
Section: Introductionmentioning
confidence: 99%